Ownership of latrine in the household in Indonesia: a review - Dyah Suryani; Abil Rudi; Hairil Akbar; Hizriansyah Hizriansyah; Maretalinia Maretalinia; Suyitno Suyitno (International Journal of Public Health Science (IJPHS), 2022)
Ownership of a household latrine has been proven to be associated with various diseases, including diarrhea. This study aimed to understand the factors related to ownership of latrine in the household, Indonesia. This study used a literature review design by collecting 15 articles screened according to the inclusion and exclusion criteria using the preferred reporting items for systematic review and meta-analysis (PRISMA) Model. It was found that attitude was significantly related to ownership of healthy latrines in the household. The level of knowledge, family income, the level of education, and the role of health practitioner were also the most significant variables in Indonesia during 2010 to 2020. The government needs to make the sanitation campaign and creative intervention to reach 100% open defecation free in Indonesia.